AN INNOVATION OF TEACHER’S SELF-ASSESSMENT OF RAPPORT BUILDING IN EFL CLASSROOM - Muhamad Nova; Didi Sukyadi (Proceedings Education and Language International Conference, 2017)
There is a need to build rapport in classroom interaction since it influences the language learning process. To build rapport, EFL teacher needs to conduct several activities. By providing a self-assessment, the EFL teacher can monitor and evaluate their own teaching to fulfill the needs of building rapport in classroom. However, any researchers have not developed the instrument of teacher’s self-assessment of rapport building in EFL classroom. Therefore, this study was established to fill the need of self-assessment instrument for building rapport in classroom by constructing a self-assessment for teacher in building rapport in EFL classroom. By applying design research from a curriculum perspective, the results revealed a self-assessment instrument of maintaining rapport for EFL teacher consisted of eleven sections with 35 statements. The Cronbach’s alpha coefficient (α= .928) of this instrument indicated high reliability and the instrument can be considered as a reliable instrument to be used for the study sample. EFL teacher needs to do self-monitoring and self-evaluation on their rapport building in classroom interaction using this instrument. Furthermore, EFL teacher can reflect on their own teaching and find additional activities to enhance positive rapport to foster positive learning environment. Additionally, further research in investigating the effect of using this instrument in assessing teacher’s quality on rapport building is required. Keywords: Rapport, rapport in EFL classroom, teacher’s self-assessment, teacher development